Design project 1968/9: report of assembly process committee - College of Aeronautics, (Cranfield) (College of Aeronautics)
This report describes the approach to the design of an automatic versatile assembly machine of modular construction. Details of the design of the conveyor module, the platen upon which the assembly is mounted and the platen motivation mechanisms are included. It also includes the assembly system that has been applied to the assembly of an electrical contact block. This entailed a machine layout, the re-design of a component and the design and specification of appropriate fixing heads.